ANXA1sp Protects against Sepsis-Induced Myocardial Injury by Inhibiting Ferroptosis-Induced Cardiomyocyte Death via SIRT3-Mediated p53 Deacetylation - Song Qin; Yingcong Ren; Banghai Feng; Xiaoqin Wang; Junya Liu; Jie Zheng; Kang Li; Miao Chen; Tao Chen; Hong Mei; Xiaoyun Fu (Mediators of Inflammation)
Sepsis-induced myocardial injury (SIMI), a common complication of sepsis, may cause significant mortality. Ferroptosis, a cell death associated with oxidative stress and inflammation, has been identified to be involved in SIMI. This study sought to investigate the role of ANXA1 small peptide (ANXA1sp) in SIMI pathogenesis. In this study, the mouse cardiomyocytes (H9C2 cells) were stimulated with lipopolysaccharide (LPS) to imitate SIMI in vitro. It was shown that ANXA1sp treatment substantially abated LPS-triggered H9C2 cell death and excessive secretion of proinflammatory cytokines (TNF-α, IL-1β, and IL-6). ANXA1sp pretreatment also reversed the increase of ROS and MDA generation as well as the decrease of SOD and GSH activity in H9C2 cells caused by LPS treatment. In addition, ANXA1sp considerably eliminated LPS-caused H9C2 cell ferroptosis, as revealed by the suppression of iron accumulation and the increase in GPX4 and FTH1 expression. Furthermore, the ameliorative effects of ANXA1sp on LPS-induced H9C2 cell damage could be partially abolished by erastin, a ferroptosis agonist. ANXA1sp enhanced SIRT3 expression in LPS-challenged H9C2 cells, thereby promoting p53 deacetylation. SIRT3 knockdown diminished ANXA1sp-mediated alleviation of cell death, inflammation, oxidative stress, and ferroptosis of LPS-treated H9C2 cells. Our study demonstrated that ANXA1sp is protected against LPS-induced cardiomyocyte damage by inhibiting ferroptosis-induced cell death via SIRT3-dependent p53 deacetylation, suggesting that ANXA1sp may be a potent therapeutic agent for SIMI.